Who is Eresus tristis Kroneberg, 1875 (Aranei: Eresidae)? - Marusik YM; Azarkina GN (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
The male palp of the holotype of Eresus tristis Kroneberg, 1875, a species considered a junior synonym of E. kollari Rossi, 1846, is illustrated. A comparison with the palp of E. kollari reveals clear differences, and therefore E. tristis is revalidated. The previously unknown type locality is recognized as southernmost Kazakhstan. All literature records of E. tristis are surveyed, and it seems that records from Eastern Kazakhstan and Xinjiang (China) refer to an undescribed species.